2003
DOI: 10.1073/pnas.242735399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of inherited hypertension with hyperkalemia: The Na–Cl cotransporter is inhibited by wild-type but not mutant WNK4

Abstract: Mutations in the serine-threonine kinases WNK1 and WNK4 [with no lysine (K) at a key catalytic residue] cause pseudohypoaldosteronism type II (PHAII), a Mendelian disease featuring hypertension, hyperkalemia, hyperchloremia, and metabolic acidosis. Both kinases are expressed in the distal nephron, although the regulators and targets of WNK signaling cascades are unknown. The Cl ؊ dependence of PHAII phenotypes, their sensitivity to thiazide diuretics, and the observation that they constitute a ''mirror image''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
352
3
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(371 citation statements)
references
References 21 publications
14
352
3
2
Order By: Relevance
“…The thiazide-sensitive Na-Cl co-transporter (NCC) in the distal convoluted tubule accounts for ~15% of sodium chloride reabsorption in the kidney. It was reported that wild type WNK4 inhibits the activity of NCC and disease-causing WNK4 mutants fail to inhibit NCC (Wilson et al, 2003;Yang et al, 2003). In addition, WNK4 phosphorylates claudins 1-4, the tight-junction proteins involved in the regulation of paracellular ion permeability (Kahle et al, 2004;Yamauchi et al, 2004).…”
Section: Pathogenesis Of Hypertension In Pha IImentioning
confidence: 99%
See 1 more Smart Citation
“…The thiazide-sensitive Na-Cl co-transporter (NCC) in the distal convoluted tubule accounts for ~15% of sodium chloride reabsorption in the kidney. It was reported that wild type WNK4 inhibits the activity of NCC and disease-causing WNK4 mutants fail to inhibit NCC (Wilson et al, 2003;Yang et al, 2003). In addition, WNK4 phosphorylates claudins 1-4, the tight-junction proteins involved in the regulation of paracellular ion permeability (Kahle et al, 2004;Yamauchi et al, 2004).…”
Section: Pathogenesis Of Hypertension In Pha IImentioning
confidence: 99%
“…Wild type WNK4 also decreases surface expression of ROMK1 and WNK4 mutants that cause disease exhibit a greater inhibition of ROMK (Kahle et al, 2003;He et al, 2007), suggesting that increased inhibition of ROMK1 by mutant WNK4 may also contribute to hyperkalemia in PHA II patients with WNK4 mutations. Recent studies using transgenic and knock-in mice models, however, reported no detectable difference in the expression of ROMK between wild type mice and mice carrying transgenic or knock-in WNK4 mutant (Lalioti et al, 2006;Yang et al, 2007).…”
Section: Pathogenesis Of Hyperkalemia In Pha IImentioning
confidence: 99%
“…In contrast, activation of WNK1 inhibits the WNK4-mediated suppression of NCC transporter translocalization ( Fig. 8; Yang et al 2003;Wilson et al 2003) and requires kinase activity of WNK1.…”
Section: Gordon's Syndrome (Pseudohypoaldosteronism Type Ii)mentioning
confidence: 99%
“…The lack of effect of cGMP and wortmannin indicates that neither PKG nor PI3K play a role in hNCC-mediated Na ϩ uptake. Recently, the serinethreonine kinase WNK4 was shown to associate with NCC and to reduce NCC membrane expression and NCC-mediated Na ϩ uptake after coexpression in Xenopus laevis oocytes (41).…”
Section: Discussionmentioning
confidence: 99%